Comparison of C‐reactive protein concentrations in dogs with Bordetella bronchiseptica infection and aspiration bronchopneumonia - Canonne, Aude Morgane (J Vet Intern Med, 2021)
BACKGROUND: C‐reactive protein (CRP) is a well‐known acute‐phase protein in dogs that may discriminate bacterial bronchopneumonia from other pulmonary conditions. Bronchopneumonia caused by Bordetella bronchiseptica (Bb) is common but the associated increase in CRP concentration in naturally infected dogs has not been fully explored. OBJECTIVE: To compare CRP concentrations of dogs with Bb infection, with or without radiographic pulmonary lesions, to dogs with aspiration bronchopneumonia (ABP). ANIMALS: Sixteen dogs with Bb infection and 36 dogs with ABP. METHODS: Retrospective study. C‐reactive protein concentrations and thoracic radiographs were available for each dog. RESULTS: Eleven dogs with Bb infection had alveolar lesions. In all dogs, CRP concentration was mildly increased (14‐38 mg/L). In the 5 dogs without alveolar lesions, CRP concentration was within the reference range in all but 1 dog, in which it was slightly increased. Median CRP concentration was significantly higher in dogs with alveolar lesions (20 mg/L) compared with dogs without alveolar lesions (5 mg/L; p < .002). In dogs with Bb infection, median duration of clinical signs was not different between dogs with normal CRP concentration and dogs with increased concentration. In dogs with Bb infection either with or without alveolar lessions, median CRP concentration was significantly lower (20 mg/L) than in dogs with ABP (118 mg/L; p < .001). CONCLUSIONS AND CLINICAL IMPORTANCE: In contrast to dogs with APB, CRP was not a good marker for the diagnosis of dogs suspected to have bordetellosis. Confirmation of Bb infection still requires lower airway sampling.